Enhancing English reading skills and self-regulated learning through online collaborative flipped classroom: a comparative study - Wang, Ying (Frontiers in Psychology, 2023)
This research investigates the effectiveness of an online collaborative flipped classroom approach in enhancing English reading skills and self-regulated learning. The study involved a total of 71 Chinese English learners who were divided into three classes and randomly assigned to different instructional groups: a traditional instruction (TI) group (n = 24), a flipped instruction (FI) group (n = 22), and an online flipped instruction (OFI) group (n = 25). The participants' reading comprehension ability was assessed using the reading section of the IELTS exam. The study employed a Self-Regulated Learning (SRL) strategy use questionnaire and weekly online quizzes to evaluate the participants' understanding of the online course materials. Additionally, the research examined participants' online learning behaviors via considering online log-on times. The participants received instruction for 12 weeks, and pre-tests and post-tests were conducted to measure their progress. The results indicated that both the FI and OFI groups outperformed the TI group in terms of reading comprehension and self-regulated learning. The findings also revealed that the OFI students demonstrated superior online learning behaviors and objective performances compared to the FI students. These findings suggest that the integration of flipped and online instruction methods holds promise for improving English reading skills.